NIGHT VISION MONOCULAR - BASIC ELEMENTS AND DEVELOPMENT TRENDS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article examines the fundamental elements and evolving trends in night vision monocular devices. The topicality of this topic lies in the ongoing advancements in sensor technologies, optics, and digital processing, which continually enhance the performance and accessibility of night vision devices. The purpose of this study is to provide a comprehensive overview of the basic components and recent developments in night vision monoculars. The study adopts a comparative analysis approach, examining the key features and functionalities of different generations of night vision technology and investigates emerging trends such as miniaturization, improved image resolution, and integration with digital interfaces. The methodology involves a thorough review of literature encompassing scientific articles, patents, and technical reports related to night vision technologies. Key aspects studied include image intensifier tubes, infrared sensors, objective lenses, and display systems. Additionally, recent research articles, technical reports, and product specifications are analyzed to identify emerging trends in monocular design and performance, in digital image processing algorithms and the integration of augmented reality functionalities. The findings underscore the importance of ongoing research and development in improving the performance and accessibility of night vision monoculars. Key conclusions include the growing role of digital imaging in night vision devices, the potential for further miniaturization of components, and the importance of optimizing cost-efficiency without compromising performance. In summary, this article provides insights into the foundational components and evolving trends of night vision monoculars, emphasizing the technological advancements driving the development of next-generation night vision devices. The findings contribute to a deeper understanding of the current state and future prospects of night vision technology.